Влияние температуры на ранние этапы постэмбрионального развития прудового карпа - Татарко, К.И. (Гидробиологический журнал, 1966)
Вопрос о влиянии температуры на постэмбриональное развитие прудового карпа в литературе освещения не получил. В связи с этим на экспериментальной базе Института гидробиологии АН УССР в дендропарке «Александрия» (г. Белая Церковь, Киевской обл.) в течение 1962—1964 гг. нами проведены серии опытов по выращиванию личинок прудового карпа с момента их выклева и до перехода в мальковую стадию при разных температурах. Experiments on the growing of larvae from artificially fertilized roe of scaly carp under laboratory conditions at various temperatures of the water (from 16 to 30° C showed that:With a rise in temperature the growth and development of carp larvae increase. High temperature affects the morphogenesis of fish to a greater extent than their growth. High temperature has a more favourable effect on the appearance in fish of its individual properties — potential to intensive growth — than a low temperature. Hence, fluctuations in the size of the carp grown at early stages of post-embryonic development at a high temperature are always stronger than in carp grown at a low temperature. Growing pond carp at early post-embryonic stages of development at a high temperature makes it easier to carry out selection by the indicated valuable characters.